Computational Fluid Dynamics Simulation of Thermal Processes in Food Technology and Their Applications in the Food Industry - Arkadiusz Szpicer; Weronika Bińkowska; Adrian Stelmasiak; Magdalena Zalewska; Iwona Wojtasik-Kalinowska; Karol Piwowarski; Joanna Piepiórka-Stepuk; Andrzej Półtorak (Applied Sciences)
In this review, the application of computational fluid dynamics (CFD) simulations in analyzing thermal processes within food technology is explored. The focus is on understanding heat transfer, fluid flow, and temperature distribution during various food processing methods, such as baking, frying, pasteurization, and cooling. Detailed insights that are often challenging to obtain through experimental methods alone are provided by CFD simulations, allowing for the optimization of process parameters to enhance product quality and safety. It is demonstrated that CFD can effectively model complex thermal phenomena, providing valuable data on temperature gradients and flow patterns. These simulations assist in the designing of more efficient processing equipment, improving energy consumption, and ensuring uniform heat treatment, which is crucial for maintaining the nutritional and sensory attributes of food products. Furthermore, the integration of CFD in the food industry leads to significant advancements in product development, reducing the time and cost associated with experimental trials. Future research should focus on refining these models for greater accuracy and exploring their application in emerging food processing technologies.